Policy Reform Efforts and Equal Opportunity – An Evidence-Based Link? - Corinna Geppert; Sonja Bauer-Hofmann; Stefan Thomas Hopmann (Center for Educational Policy Studies Journal)
The main focus of the present paper is to answer two different questions: From the perspective of Austrian education policy, which core areas of schooling are linked to the demand for equal opportunity? Can these reform efforts sustain the current state of research, and what are the consequences for schooling? The paper draws on an analysis by Hopmann, Geppert & Bauer (2010). Fifteen official self-presentations (political programmes) of Austrian political parties were analysed for statements concerning the improvement of the education system. This resulted in about seventy different statements, which were aggregated into eight core areas. We conducted a systematic analysis of four of these core areas, dealing with the topics of equal opportunity: comprehensive school, all-day schooling, school autonomy and standardisation of students’ achievements. The aim was not to judge the legitimacy or the political content of the claims made. In line with evaluative discourse, we asked whether the combination of political demands and their associated expectations met the current state of research. In many policy programmes, it is assumed that comprehensive schooling, all-day schooling, education standards, standardised general certification for university attendance, school autonomy or language surveys go hand in hand with more equality of opportunity, justice and quality in education, but an analysis of the current state of research could not confirm this. The analysis showed that, with regard to education policy demands, statements having empirically little or nothing to do with each other are often linked.